Residivistis sebagai Syarat Pengecualian Diversi dalam Sistem Peradilan Pidana Anak di Indonesia - Aziz, Siti Nur Afifah; Sugiri, Bambang; Endrawati, Lucky (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
The purpose of this study was to analyze the Banyumas District Court Decision Number 05/Pid.Sus-Anak/2015/PN-Bms and analyze the recidivism concept in Indonesia's juvenile criminal justice system. This study uses a normative doctrinal method with legal, case, and conceptual approaches. The decision of the Banyumas District Court Number 05/Pid.Sus-Anak/2015/PN-Bms contained a case of abuse by a child who had previously been punished with three months in prison by the Purbalingga Court for committing the crime of theft. The concept of recidivism in the juvenile criminal justice system in Indonesia was based on Article 7 paragraph (2) letter b of Law Number 11 of 2012, which explained that children who commit recidivists could not be diverted.